Metodología para la gestión de proyectos en el Departamento de Ingeniería de la empresa Monaro Club, S.A. - Vargas-Delgado, Efrén (Instituto Tecnológico de Costa Rica, 2016)
The final graduation project that develops below, provides the basis for implementing a project management methodology in the Engineering’s Department of the company Monaro Club, S.A.; based on best practices of Project Management. In this project a current situation’s diagnosis has been performed, related to the knowledge level in Project Management that has the organization and specifically the staff of the Engineering’s Department, who will be benefited with the proposed methodology implementation. The proposed methodology elements are detailed one by one on the development of this document. The most important processes are selected according to phases of project life cycle, based on results provided by the current situation’s diagnosis and the framework that will be Project Management Body of Knowledge (PMBoK®) from the PMI®. Templates or standard formats are designed, as well as their use and implementation procedures, it is proposed that this documentation will be commonly used for development of new Engineering Department’s projects. Finally, a methodology implementation plan is proposed in the organization, which considers project culture introduction, methodology implementation and continuous improvement.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2016.
Keywords: Proyecto; Organización; Procedimientos; Implementación; Procesos